A comparison study of water diffusion in unidirectional and 2D woven carbon/epoxy composites. Issue 1 (22nd October 2021) - Almudaihesh, Faisel; Holford, Karen; Pullin, Rhys; Eaton, Mark
Abstract: The use of CFRP composites is significantly increasing in the aerospace, automotive, and marine industries, particularly in safety critical primary structures. This work presents a newly developed experimental approach to investigate the directional diffusion of water in CFRP composites with the use of Fick's law. The approach is used to study the effect of fiber architecture on directional diffusion rates, with a particular focus on the role of fiber waviness in the diffusion process. A comparison of water diffusion is made in three different fiber architectures: Unidirectional (UD), plain weave, and twill weave. The specimens were fully immersed in 90°C purified water until their maximum moisture saturation was achieved, with some specimens being selectively exposed from the edges only to obtain the directional diffusion coefficients. The water penetration process into the CFRP structure initiate from the micro‐cracks and defects. The experimental work of this study shows sharp mass increases within the first stage followed by an equilibrium stage where saturation is present. The interfacial region is found to be a critical parameter where detachment of the interfacial fiber/matrix bonding is observed further demonstrating the potential effect of different fiber architecture in this region. UD fiber architecture showed 20% higher diffusion coefficient in the Dx, y direction compared with plain and twill woven architectures. The weave patterns in 2D woven fiber architectures are therefore believed to play a key role on the moisture ingress mechanism and subsequently contributed in slowing down the capillary process in the interfacial region. This has implications for materials development and selection for CFRP composites used in moist environments.